POTENSI BEBERAPA TANAMAN ATRAKTAN DALAM PENGENDALIAN HAMA KEONG MAS (Pomacea Canaliculata Lamarck) PADA TANAMAN PADI SAWAH DI DESA TONSEWER KECAMATAN TOMPASO II - Irma Tombuku; James B. Kaligis; Mareyke Moningka; Jusuf Manueke (Universitas Sam Ratulangi, 2014)
ABSTRACKRice is an annual plant, belonging to the grasses of the Oryza genus, family of Graminae (Poaceae), with Oryza sativa L. being one of the species. Rice is the main commodity for the Indonesian people. In Indonesia, rice is an important food crop because more than half the population are dependent on rice produced by rice plants. This study aims to determine the potential of some types of plants that serve as attractants for the channeled applesnail. This research was conducted in farmers' fields in the village of Tonsewer from March to October 2013. This study uses a completely randomized design with four treatments and three replications in the research sites. Materials and tools used in this study are the leaves of banana plants, papaya, taro, and tagalolo, buckets, rough scales, plastic rope, knife, tape measure, camera and stationery. The results showed the highest population on taro leaves (106.73 individuals), followed by papaya leaves (59.53 individuals), tagalolo leaves (41.47 individuals), and the lowest population in banana leaves (38.73 individuals).Keywords: Rice, Channeled Applesnail (Pomacea canaliculata), Attractant plants